Humoral immune response against Newcastle disease virus and its pathological changes in vaccinated chickens in selected areas of Barisal district in Bangladesh (Asian Journal of Medical and Biological Research, 2020)
The objectives of this study were to evaluate humoral immunity against Newcastle disease (ND) virus in vaccinated chickens in terms of serum HI antibody titers in broiler and layer chickens and to determine pathological changes in vaccinated chickens. A total of 240 serum samples were collected from broiler (135) and layer (105) chickens from Barishal Sadar, Babugonj and Gournadi Upazilas of Barishal district in Bangladesh after two weeks of scheduled vaccination programme. The overall detection of Hemagglutination inhibition (HI) antibodies against Newcastle disease virus was 62.2% in broiler and 83.8% in layer chickens. The percentages of specific HI antibody titer in broiler chickens were 57.5, 70 and 48 in 1-2 weeks, 3-4 weeks, and 4-above weeks age groups respectively where in layer chickens were 85, 80, 90, 80 and 80 in 15-24 weeks, 25-34 weeks, 35-44 weeks, 45-54 weeks and > 55 weeks of age groups respectively. For both broiler and layer chicken’s protective antibody titers were found higher in adult than in young chickens. Out of 240 samples HI titers of 172 (71.67%) samples were found at protective level, 42 (17.5%) samples were at marginal level and 26 (10.83%) samples were below protective level. Among 26 samples of non-protective level, 21 were broiler and 5 were layer chicken. Out of 26 samples, 10 (38.46%) were found apparently infected with NDV where 8 (38.09%) were broiler and 2 (40%) were layer. The apparently infected birds were diagnosed on the basis of postmortem findings and histopathological lesions. Results of the present investigation may help to design appropriate vaccination schedule for ND in broiler and layer chickens and thus to protect chickens from ND in field condition.Asian J. Med. Biol. Res. June 2020, 6(2): 155-167